1993
DOI: 10.1095/biolreprod49.4.764
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Mouse Oocytes: Mutagenic Effects in the Embryo?1

Abstract: We have shown in previous studies that the complete cycle of cryopreservation and prefreezing manipulations increases the degeneration and decreases the fecundability of mouse oocytes. The present study confirms these results. Moreover, we show that the increase of polyploidy previously observed in one-cell zygotes derived from frozen-thawed oocytes persists during the early stages of embryonic development. Furthermore, embryos obtained from frozen oocytes or oocytes exposed to prefreezing manipulations show a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…A much larger number of studies have looked for indirect evidence of genetic damage, such as chromosomal anomalies. Enough of these studies have found evidence of such damage to be a cause for concern (Rudd et al, 1989 ;Schmidt-Preuss et al, 1990 ;Casati et al, 1992 ;Bouquet et al, 1993). The advent of cryopreservation in D. melanogaster offers a good opportunity to perform large-scale genetic analyses of the effects of such techniques in a complex metazoan.…”
Section: Introductionmentioning
confidence: 99%
“…A much larger number of studies have looked for indirect evidence of genetic damage, such as chromosomal anomalies. Enough of these studies have found evidence of such damage to be a cause for concern (Rudd et al, 1989 ;Schmidt-Preuss et al, 1990 ;Casati et al, 1992 ;Bouquet et al, 1993). The advent of cryopreservation in D. melanogaster offers a good opportunity to perform large-scale genetic analyses of the effects of such techniques in a complex metazoan.…”
Section: Introductionmentioning
confidence: 99%
“…The current opinion-that embryo freezing has no late consequencesrelies on the negative results of previous experimental studies (10)(11)(12)(13)(14)(15) and on common experience in cattle and humans. More recently, however, damage to the genetic material from freezing has been reported (16)(17)(18). Furthermore, in domestic species as in humans, investigations have mainly focused on patent defects at birth or in early life.…”
mentioning
confidence: 99%
“…Some of these effects vary as a function of strain and sex. Regarding these results, it is interesting, on the one hand, that other teams [62] as well as ourselves [63,64] have ob served, in situations with known genetic risks, similar abnormalities in systems where the genetic determination is very polygenicsuch as the CNS -and on the other hand, that, as we have shown, oocyte cryopreservation seems to lead to mutations in derived em bryos [81], Therefore, the cryopreservation of em bryos does not appear to be neutral in terms of effect. Moreover, the variations in effects from one genotype to another correspond to what is known about the forms of action of teratogenic factors [82].…”
Section: The Particular Case Of a Ssiste D Procreationsmentioning
confidence: 59%